2015
DOI: 10.1007/s13679-015-0179-2
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Physical Activity: The Importance of Play and Nature-Based Play Spaces for Children’s Health and Development

Abstract: The reduction of child obesity continues to be a challenge worldwide. Research indicates that playing outdoors, particularly in natural play spaces, boosts children's physical activity, potentially decreasing childhood obesity. We present evidence that natural play spaces also provide for more diverse forms of play for children of varying ages and competencies. This is crucial because play spaces designed expressly for physical activity may not increase physical activity among less active children. Moreover, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 43 publications
(40 reference statements)
4
113
0
8
Order By: Relevance
“…In addition to the importance of PA for children's health and wellbeing, spending time outdoors and engaging in activities such as play has been demonstrated to improve emotional and social resilience in children [6,7]. Play is an essential part of childhood as it facilitates developmental outcomes, such as gross motor skills, as well as cognitive and social development [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the importance of PA for children's health and wellbeing, spending time outdoors and engaging in activities such as play has been demonstrated to improve emotional and social resilience in children [6,7]. Play is an essential part of childhood as it facilitates developmental outcomes, such as gross motor skills, as well as cognitive and social development [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Literature has indicated that promoting outdoor play can have a significant impact on children's physical activity (Harrington and Brussoni, 2015), which in turn improves blood pressure, cholesterol, and bone density (Lewicka and Farrell, 2007; Copeland et al, 2012), contributing to the reduction and prevention of child obesity (Raustorp et al, 2012). Children are more physically active when playing outdoors.…”
Section: Introductionmentioning
confidence: 99%
“…A szabadban zajló játéktevékenység személyiségfejlődésre gyakorolt hatásai, a környezet által kínált lehetőségek és a személyes beállítódások összefüggésében A veszély elkerülése, a biztonságos helyek megközelítése, és a szabadban zajló játék kiemelt szerepet kap az otthontól távoli környezet megismerésé-ben és a személyes adaptációs lehetőségek kiteljesedésében (Kyttä, 2003;Lester & Maudsley, 2007). Más tanulmányok a gyermekek motoros funkció-inak fejlődése és a fizikai egészség fenntartása szempontjából emelik ki a spontán szabadtéri játék meghatározó szerepét (Herrington & Brussoni, 2015;Spencer & Wright, 2014). Prezza és munkatársainak (2007) eredmé-nyei szerint azok a gyermekek, akik többet játszanak szabadban, általában többet játszanak házon belül is kortársaikkal.…”
Section: Korlátozó éS Fejlesztő Környezeti Feltételek a Gyermekkori Junclassified
“…A biztonsággal és felügyelettel kap-csolatos problémát a gyermekek nagyobb és szervezettebb, az esetek több-ségében formális csoportokba integrálásával kívánják megoldani. Ilyen kö-rülmények között az ellenőrzés, a szülők elérésének lehetősége elősegíti ugyan a játék kibontakozását, de ugyanakkor hátráltatja is az autonómia és egyes szociális kompetenciák fejlődését (Herrington & Brussoni, 2015;Herrington és mtsai, 2007). Adataink erre a tényre is ráirányítják a figyelmet.…”
Section: Játéktípus éS Félelemunclassified